2016
DOI: 10.1038/srep38102
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Acetylcholinesterase2 (ace2) increase the insensitivity of acetylcholinesterase to fosthiazate in the root-knot nematode Meloidogyne incognita

Abstract: The root-knot nematode Meloidogyne incognita causes severe damage to continuously cropping vegetables. The control of this nematode relies heavily on organophosphate nematicides in China. Here, we described resistance to the organophosphate nematicide fosthiazate in a greenhouse-collected resistant population (RP) and a laboratory susceptible population (SP) of M. incognita. Fosthiazate was 2.74-fold less toxic to nematodes from RP than that from SP. Quantitative real-time PCR revealed that the acetylcholinest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…At present, chemical control is the main control measure, but many nematicides are banned because of safety, ecological, and environmental concerns [3]. However, there are many shortcomings in the limited control categories, such as fosthiazate, which can lead to high toxicity to non-target organisms [4] and drug resistance [5,6] and avermectin, which has difficulty to stay structurally unstable [7] and poor mobility in soil. Therefore, it is critical to develop novel types of eco-friendly and highly efficient nematicides.…”
Section: Introductionmentioning
confidence: 99%
“…At present, chemical control is the main control measure, but many nematicides are banned because of safety, ecological, and environmental concerns [3]. However, there are many shortcomings in the limited control categories, such as fosthiazate, which can lead to high toxicity to non-target organisms [4] and drug resistance [5,6] and avermectin, which has difficulty to stay structurally unstable [7] and poor mobility in soil. Therefore, it is critical to develop novel types of eco-friendly and highly efficient nematicides.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to benzimidazoles in the animal parasitic nematode Haemonchus contortus is the result of point mutations (F200Y with F167Y or E198A) within β-tubulin 19 . The presence of 18 point mutations in AChE2 has also been shown to be associated with the fosthiazate resistance in the plant-parasitic nematode, M. incognita 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Animal parasitic nematode Haemonchus contortus displaying resistance to benzimidazoles has also been proved to be the result of point mutations on the target site protein β-tubulin (F200Y with F167Y or E198A) 19 . The plant-parasitic nematode, M. incognita has been reported that 18 point mutations in AChE2 are associated with the fosthiazate resistance 20 .…”
Section: Introductionmentioning
confidence: 99%